Variability in Susceptibility to Anthracnose in the World Collection of Olive Cultivars of Cordoba (Spain) - Moral, Juan; Xaviér, Carlos J.; Viruega, José R.; Roca, Luis F.; Caballero, Juan; Trapero, Antonio (Frontiers in Plant Science, 2017)
Anthracnose of olive (Olea europaea ssp. europaea L.), caused by Colletotrichum species, is a serious disease causing fruit rot and branch dieback, whose epidemics are highly dependent on cultivar susceptibility and environmental conditions. Over a period of 10 years, there have been three severe epidemics in Andalusia (southern Spain) that allowed us to complete the assessment of the World Olive Germplasm Bank of Córdoba, one of the most important cultivar collections worldwide. A total of 308 cultivars from 21 countries were evaluated, mainly Spain (174 cvs.), Syria (29 cvs.), Italy (20 cvs.), Turkey (15 cvs.), and Greece (16 cvs.). Disease assessments were performed using a 0-10 rating scale, specifically developed to estimate the incidence of symptomatic fruit in the tree canopy. Also, the susceptibility of five reference cultivars was confirmed by artificial inoculation. Because of the direct relationship between the maturity of the drupes and their susceptibility to the pathogen, evaluations were performed at the end of fruit ripening, which forced coupling assessments according to the maturity state of the trees. By applying the cluster analysis to the 308 cultivars, these were classified as follows: 66 cvs. highly susceptible (21.4%), 83 cvs. susceptible (26.9%), 66 cvs. moderately susceptible (21.4%), 61 cvs. resistant (19.1%), and 32 cvs. highly resistant (10.4%). Representative cultivars of these five categories are ‘Ocal’, ‘Lechín de Sevilla’, ‘Arbequina’, ‘Picual’, and ‘Frantoio’, respectively. With some exceptions, such as cvs. Arbosana, Empeltre and Picual, most of the Spanish cultivars such as ‘Arbequina’, ‘Cornicabra’, ‘Hojiblanca’, ‘Manzanilla de Sevilla’, ‘Morisca’, ‘Picudo’, ‘Farga’, and ‘Verdial de Huévar’ are included in the categories of moderately susceptible, susceptible or highly susceptible. The phenotypic evaluation of anthracnose reaction is a limiting factor for the selection of olive cultivars by farmers, technicians, and breeders.